2003
DOI: 10.1016/s0002-9440(10)64327-1
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinase A (MMP-2) Is Necessary and Sufficient for Renal Tubular Cell Epithelial-Mesenchymal Transformation

Abstract: Progressive renal interstitial fibrosis and tubular atrophy represent the final injury pathway for all commonly encountered forms of renal disease that lead to end-stage renal failure. It has been recently recognized that myofibroblastic cells are the major contributors to the deposition of interstitial collagens. While there are several potential cellular sources of myofibroblasts, attention has focused on the transformation of the organized tubular epithelium to the myofibroblastic phenotype, a process poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
205
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(220 citation statements)
references
References 69 publications
10
205
1
4
Order By: Relevance
“…Glomerulosclerosis and tubulointerstitial fibrosis in 4M and 12M DSS rats aging (17,23,37). Recent studies have shown that in addition to excessive synthesis of the ECM, the presence of amorphous ECM deposits in progressive renal disease are due to decreased activity of the ECM degradative pathway (38,39). Our studies extend these findings by providing evidence of decreased activity of MMP, specifically MMP-9 and MMP-2, in the 12M kidney, thus contributing to the age-related accumulation of ECM in tubulointerstitial fibrosis and glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerulosclerosis and tubulointerstitial fibrosis in 4M and 12M DSS rats aging (17,23,37). Recent studies have shown that in addition to excessive synthesis of the ECM, the presence of amorphous ECM deposits in progressive renal disease are due to decreased activity of the ECM degradative pathway (38,39). Our studies extend these findings by providing evidence of decreased activity of MMP, specifically MMP-9 and MMP-2, in the 12M kidney, thus contributing to the age-related accumulation of ECM in tubulointerstitial fibrosis and glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The CTT peptide has also been used to modify the natural tropism of adenovirus for a therapeutic gene delivery in a rabbit restenosis model (Turunen et al, 2002). In addition, CTT peptide has been used to localize gelatinase activity in tissue samples using in situ zymography (Pirilä et al, 2001), and to evaluate the contribution of gelatinases in various biological processes including vasoconstriction, epithelial-mesenchymal transition and hepatitis (Cheng and Lovett, 2003;Fernandez-Patron et al, 2000;Franzke et al, 2002).…”
Section: Synthetic Gelatinase Inhibitorsmentioning
confidence: 99%
“…The role of MMPs as EMT inducers has been described in kidney, lung, ovary, oral, and mammary epithelium [52][53][54][55][56][57]. Their mechanism of action involves the processing and activation of pro-TGF-β in the ECM, as well as the direct proteolysis of E-cadherin [53,55,57].…”
Section: The Epithelium To Mesenchymal Transitionmentioning
confidence: 99%